Implementation of the Simple Additive Weighting Method in Determining Promotional Locations for Prospective New Student Admissions in Colleges - Kurniawijaya, Putu Andhika; Karsana, I Wayan Widi (Yayasan Kita Menulis, 2024)
Universities are currently competing in the selection of prospective students. By attracting high school graduates and others to continue their education to a higher level of education, universities promote high schools and vocational schools in the surrounding area. Every year, universities actively conduct promotional activities to gain the capacity that has been targeted by university leaders. One of the obstacles faced by universities in achieving the promotion target is the number of high schools and vocational schools spread across all provinces in Indonesia. The promotion section in determining the target area of promotion is requested by university leaders to be right on target because the budget of each university is limited. Determining the right promotion target can help universities strategize and use the budget appropriately and efficiently. The Simple Additive Weighting (SAW) method was chosen because it has an easy-to-understand concept. The criteria used in this study are: 1) the number of private universities in the district; 2) the number of high schools and vocational schools in the district; 3) the number of students in the district; and 4) the distance of private universities from the district.